2020
DOI: 10.1098/rsos.200844
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the glycan of receptor binding domain with jacalin as a novel approach to develop a treatment against COVID-19

Abstract: In silico analysis revealed that a lectin, jacalin from jackfruit seeds, recognizes a glycosylated region of the receptor-binding domain (RBD) of SARS-CoV2. Jacalin binding induces conformational changes in RBD and significantly affects its interaction with human angiotensin-converting enzyme 2. The result may open up exploration of lectin-based strategies against COVID-19.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Pokhrel et al 46 mentioned that the only asparagine conserved in several variants and mutations found in spike RBD structure N‐glycosylation sites is Asn‐343. Rajendaran et al 30 suggested that this ligand site is a good key to developing therapies against COVID‐19. CLEC5A structures do not have any special ligand site but can interact with the structures of several viruses, and its expression is related to lethality 1,3,4 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pokhrel et al 46 mentioned that the only asparagine conserved in several variants and mutations found in spike RBD structure N‐glycosylation sites is Asn‐343. Rajendaran et al 30 suggested that this ligand site is a good key to developing therapies against COVID‐19. CLEC5A structures do not have any special ligand site but can interact with the structures of several viruses, and its expression is related to lethality 1,3,4 .…”
Section: Discussionmentioning
confidence: 99%
“…The retained poses were then clustered, and the top poses were assessed. After the docking prediction by Cluspro, the interactions between the CLEC5A receptor and spike protein were visualized using PyMOL software (http://www.pymol.org/pymol), 30 which provided the binding residue prediction, as well as the root‐mean‐square deviation (RMSD). The RMSD was calculated by superimposition between the ligands atoms in the model provided by ClusPro top poses.…”
Section: Methodsmentioning
confidence: 99%
“…In silico study showed that jacalin from jackfruit seeds binds to the glycosylated region of the receptor-binding domain (RBD) of SARS-CoV2 and alters its conformation. The conformation change in RBD affects their binding to human angiotensin-converting enzyme 2, suggesting the inhibitory potential of jacalin [ 13 ]. The water-soluble lectin from Moringa oleifera seeds (WSMoL) alters the membrane permeability to exhibit growth inhibition activity (5.2–167 μg/mL) against Bacillus sp.…”
Section: Lectins As Inhibitorsmentioning
confidence: 99%
“… Specificity Bioactivity Ref. Banana lectin BanLec Mannose/glucose HIV-1 inhibitor [ 12 ] Jacalin Jacalin Galactose SARS-CoV2 inhibitor [ 13 ] Moringa oleifera seeds WSMoL Fructose and porcine thyroglobulin Antibacterial [ 14 ] Lantana camara lectin LCL Asialo mucin, melibiose, chitin, methyl α,D galactopyranoside Antibacterial, antifungal [ 15 ] Andrias davidianus lectin ADL Porcine submaxillary glycoprotein (PSM), asialo-PSM Antibacterial [ 16 ] Bauhinia variegata lectin BVL–I Lactose, galactose and D-GalNAc Antibiofilm [ 17 ] Calliandra surinamensis leaves lectin CasuL ovalbumin, fetuin and bovine serum albumin Antibacteria, antibiofilm, antifungal, cytotoxic [ 18 ] Jackin Jackin Chitin Antifungal [ 19 ] Frutackin Frutackin Chtiin Antifungal [ 19 ] Chondrilla caribensis lectin <...…”
Section: Introductionmentioning
confidence: 99%
“…Protein-protein docking was also carried out to predict the binding affinity of ERβ-MDM2 complex in the presence of ergotamine using web server ClusPro 2.0 (Jena & Duttaroy, 2022;Rajendaran, et al, 2020). The binding affinity of the complex showed a lower score than of ERβ-MDM2 without ergotamine (see Table 1 and 4).…”
Section: Ergotamine Binds To Estrogen Receptor Beta (Erβ) and Murine ...mentioning
confidence: 99%